Radioactivity concentration of natural and anthropogenic radionuclides in the soil of Banswara region, Rajasthan and associated radiation index parameters - Rajpal Gill; Balram Meena; Shailesh Nath Tiwari; I. V. Saradhi; A. Vinod Kumar (Radiation Protection and Environment)
Activity concentrations of gamma-emitting naturally occurring radionuclides (NORM’s) of 226Ra, 232Th, and 40K along with anthropogenic radionuclides of 137Cs in soil samples collected around the new upcoming nuclear power plant site at Banswara district, of Rajasthan, India were estimated. The mean radioactivity concentrations of 226Ra, 232Th, 40K, and 137Cs in surface soil samples of Banswara region were 17.6, 36.4, 309.7, and 1.4 Bq.kg−1, respectively. The mean activity of 226Ra, 232Th, and 40K is lower when compared to the world average values. Average radium equivalent activity (Raeq), absorbed gamma dose rates in air (DR), and annual effective dose (AED) for the soil of the study area are calculated as 94.0 Bq.kg−1, 43.0 nGy.h−1, and 0.26 mSv.y−1, respectively. Estimated AED to the general public is 0.24 mSv.y−1, which is comparable to the global values due to terrestrial radiation. These radiological index parameters were compared with internationally approved values and the recommended safety limits. The study and analysis of collected soil samples from the Banswara region of Rajasthan indicate that the soil of this area does not pose any significant radiological health hazard to the people residing in adjacent areas. Multivariate Statistical analysis of Pearson correlation and analysis of variance (ANOVA) has been carried out. The result of ANOVA test indicated that there is no remarkable difference in the total variance of radioactivity of NORMs with respect to distance and it also indicated that the soil of the area belongs to a similar lithologic origin. The Pearson correlation of 226Ra with 232Th (r = 0.53) and 40K (r = 0.68) showed a fairly positive correlation, suggesting that their content in soil samples were mostly influenced and controlled by sources of similar origin. Spatial distribution maps using the kriging interpolation algorithm have been generated for the 30 km × 30 km area.